3
$\begingroup$

I was trying to solve the equation, $x=1+\sqrt{x}$ for real $x$. Though I didn't correctly solve it. I'm curious as to why that is, and what else I need to initially consider in the domain of the function.

I started off by recognising that $x \geq 0$ for the square root to be real (I know when $x=0$ it is not a solution). Squaring both sides and rearranging; $$x^2 -3x + 1=0$$ Finding the solutions to this equation you obtain; $x=\frac{3\pm\sqrt{5}}{2}$. Both of these solutions to that equation are greater than zero, but only $x=\frac{3 + \sqrt{5}}{2}$ is the solution to the original. Why is that?

Is there some other "domain" restriction I must consider? Or for every question where there inolves root must I numerically test it (is there no way to get around this)?

Thanks

$\endgroup$
  • $\begingroup$ Actually $x-1=\sqrt(x)≥0$ and hence x≥1 rather than 0. So there is only one root. $\endgroup$ – Huang Apr 29 '17 at 2:30
  • $\begingroup$ You x has to be one more than its square root. That's impossible if x is less than 1. $\endgroup$ – fleablood Apr 29 '17 at 2:30
  • 1
    $\begingroup$ The question is where does the extraneous solution slip in. Apparently not at x >=0. But first step is $x-1=\sqrt {x} >=0$ so.. $x >= 1$. So that's where it slips in. $\endgroup$ – fleablood Apr 29 '17 at 2:38
8
$\begingroup$

When you square an equation, you lose information. In your case, the equation $x -1 = \sqrt{x}$ will result in the same equation as $x-1 = -\sqrt{x}$ after squaring both sides: $(x-1)^2 = x$, regardless of the domain $x\geq 0$.

So your two roots $x = \frac{1}{2}(3 \pm \sqrt{5})$ come from one of them being a solution to $x-1 = -\sqrt{x}$ and the other $x-1 =\sqrt{x}$, even if both equations have domain $x \geq 0$.

For an answer to your last question, yes, in such cases, you'll need to check that any solution set you get from an equation after squaring it isn't a spurious solution by checking that it satisfies the original equation. To clarify this: it needn't be checking numerically - there are certain conditions you can check, for example as in law-of-fives comment, you have $x-1 =\sqrt{x} > 0$ so the only valid solution is the one that satisfies $x>1$.

$\endgroup$
  • $\begingroup$ It suffices to note that $\sqrt{x}$ must be positive given the original problem and when $x$ is found through the quadratic equation, given your first equation we not only have the criterion $x>0$ but also $x-1>0$. $\endgroup$ – law-of-fives Apr 29 '17 at 2:28
3
$\begingroup$

Let $y=\sqrt x\ge0$

$$\implies y^2=1+y\iff y^2-y-1=0$$

Clearly, the two roots are of opposite signs.

Now solve the quadratic equation.

$\endgroup$
  • 4
    $\begingroup$ This doesn't address the OP's question. $\endgroup$ – mrnovice Apr 29 '17 at 2:34
1
$\begingroup$

In general you "slip" the domain restiction at the exact point you square both sides.

$x=1+\sqrt {x} $

$x-1=\sqrt {x} $

!!! Here!! ===> $(x-1)^2=\sqrt {x}^2$<=== !!! Here!!! (so $x-1\ge 0$)

And with that in mind.....

$\endgroup$
1
$\begingroup$

The equation $x=1+\sqrt x$ can be rewritten as $x - \sqrt x - 1 = 0$. Hence the solution to the equation $x=1+\sqrt x$ is the root of the function

$$y = x - \sqrt x - 1 $$

Notice that $\sqrt x$ requires $x \ge 0$. The red plot below is the graph of the function $y = x - \sqrt x - 1$. We are interested in where this graph crosses the $x$-axis (since that's where $y=0$).

enter image description here

Let's rewrite the equation by eliminating the square root term.

\begin{align} y &= x - \sqrt x - 1 \\ \sqrt x &= x - y - 1 \\ x &= x^2 - 2xy + y^2 -2x + 2y + 1 \\ x^2 - 2xy + y^2 -3x + 2y + 1 &= 0 \end{align}

The equation

$$x^2 - 2xy + y^2 -3x + 2y + 1 = 0$$

is the equation of a parabola and is shown as a black dotted line on the plot above. Note that this equation is a extension (or a completion) of the original equation.

When you solved for $x$, you got the points $(\frac 12(3 \pm \sqrt 5), 0)$, one of which is on the red plot and one of which is not but both points are on the parabola.

Note also that

$$x^2 - 2xy + y^2 -3x + 2y + 1 = (x-y-1 - \sqrt x)(x-y-1 + \sqrt x)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.